2020
DOI: 10.1177/1082013220956739
|View full text |Cite
|
Sign up to set email alerts
|

Compositional characteristics of cherry kernel oil as influenced by gamma irradiation and storage periods

Abstract: This research work was undertaken to evaluate the physicochemical parameters of oil from the cherry kernel non-irradiated and irradiated at 3 and 6 kGy of gamma irradiation for two storage periods (0 and 12 months). The acid value, peroxide value, thiobarbituric acid reactive substances value, iodine value, saponification value refractive index (peroxide value), and the color parameters of cherry kernel oils were determined. The results indicated that the extracted cherry kernel oils were liquid at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Iodine values (IVs), peroxide values (POVs) and acid values (AVs) are often used as the indicators for the oxidative stability of fats and oils [ 17 , 22 ]. They are becoming significance for the assessment of quality and stability of oils [ 16 , 17 ]. Many studies have shown that the oil was to hydrolyze, to oxidize, to decompose and to undergo rancidity by physical and chemical changes after being used long heat time [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine values (IVs), peroxide values (POVs) and acid values (AVs) are often used as the indicators for the oxidative stability of fats and oils [ 17 , 22 ]. They are becoming significance for the assessment of quality and stability of oils [ 16 , 17 ]. Many studies have shown that the oil was to hydrolyze, to oxidize, to decompose and to undergo rancidity by physical and chemical changes after being used long heat time [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…POV is one of the most typically used quality parameters to monitor lipid oxidation. AV is common measure of the breakdown of the triacylglycrols into free fatty acids, which has an adverse effect [ 15 , 16 ]. Therefore, the objective of this study was to research the effect of heating on the quality characteristics of Bohai algae oil comparison with soybean oil (always for high-temperature cooking) and olive oil (not survive high-temperature cooking) using the IVs, POVs and AVs.…”
Section: Introductionmentioning
confidence: 99%
“…Surface colour measurements refer to the method of Al‐Bachir & Koudsi (2021). The Δ E was calculated using the following equation (eqn 1):ΔE=ΔL*2+Δa*2+Δb*2, where L *, a * and b * are the lightness ( L *), greenish‐reddish ( a *), and yellowish‐bluish ( b *).…”
Section: Methodsmentioning
confidence: 99%
“…The most reported extraction strategies focus on classical extraction by nonpolar organic solvents 5,19,20,[22][23][24][25] or extraction via supercritical carbon dioxide (scCO 2 ) 10,13,20,21 with and without the use of co-solvent. Although the application of classic organic solvent extraction is relatively simple, it has the disadvantage of a high environmental impact.…”
Section: Introductionmentioning
confidence: 99%